Peningkatan Kemampuan Membaca Menggunakan Media Gambar Siswa Kelas Satu SDN 4 Mrayan Tahun Pelajaran 2023-2024 - Wah Yudi; Tamrin Fathoni (https://ejournal.insuriponorogo.ac.id/, 2024)
This research aims to determine the increase in reading ability Using Image Media for Grade 1 Students of Mrayan 4 State Elementary School for the 2023/2024 academic year. This type of research is classroom action research. The research subjects in this research are Grade 1 Students at State Elementary School 4 Mrayan for the 2023/2024 academic year. To collect data on students' reading ability results, a reading ability test instrument is used based on predetermined criteria and indicators. The results of the research show: in cycle I the average student reading ability was 65.85 and the percentage level of completion reached 55% with a medium level of ability. In cycle II the average student reading ability increased to 76 and the level of ability was relatively high with a completion level reaching 85% in accordance with the target set by researchers, namely 80%. Based on the results of data analysis, it can be concluded that the application of image media in learning can improve students' reading skills in class I at SDN 4 Mrayan for the 2023/2024 academic year.